Anticipating a Second Wave of Standards-Based Grading Implementation and Understanding the Potential Barriers: Perceptions of High School Principals. (December 2019) - Townsley, Matt; Buckmiller, Tom; Cooper, Robyn
As secondary school leaders consider a shift toward standards-based grading (SBG) practices, they are no doubt weighing the odds of a successful implementation process. This research followed up on a study from 2014 to identify the challenges secondary school leaders experience when changing the currency of the classroom from points to learning. The results indicated that the game is changing and a new wave of SBG implementation is on the horizon.